Reading ability is negatively related to Stroop interference. - Protopapas, Athanassios; Archonti, Anastasia; Skaloumbakas, Christos (Cognitive Psychology, 2007)
Stroop interference is often taken as evidence for reading automaticity even though young and poor readers, who presumably lack reading automaticity, present strong interference. Here the relationship between reading skills and Stroop interference was studied in a 7th-grade sample. Greater interference was observed in children diagnosed with reading disability (dyslexia) than in unimpaired children. Moreover, poorer reading skills were found to correlate with greater Stroop interference in the general school population. In correlation and regression analyses, interference was primarily associated with reading speed, with an additional unique contribution of reading accuracy. Color naming errors were few and not comparably related to reading skills. The relation of reading skill to Stroop interference was examined in computational modeling simulations. The production model of Roelofs [Roelofs, A. (2003). Goal-referenced selection of verbal action: modeling attentional control in the Stroop task. Psychological Review, 110, 88-125], in which interference is primarily due to word stimuli having direct access to word form encoding whereas color naming must pass through concept activation and lemma selection, was found to account well for the human data after imposing covariation constraints on parameters controlling word processing and blocking latency, in modifications not affecting the model's previous fit to other data. The connectionist model of Cohen, Dunbar, and McClelland [Cohen, J. D., Dunbar, K., & McClelland, J. L. (1990). On the control of automatic processes: a parallel distributed processing account of the Stroop effect. Psychological Review, 97, 332-361], in which interference is caused by differential route strength, implementing an automaticity account, approximated the observed patterns with network-wide parameter manipulations not specific to reading, such as processing speed and response threshold, likely to affect previously optimized performance. On the basis of the empirical and modeling data we argue for a direct link between reading skill and interference, beyond the effects of executive functioning. Copyright (c) 2007 Elsevier Inc.